Integrating Servqual-Kano-QFD for Social Insurance Service Quality Improvement in Surabaya - Dwi Dini Pratiwi (Universitas Airlangga, 2021)
For companies engaged in the service-providing sector, good service by meeting customer's desires and needs is a must in order to thrive competitively. This case study was conducted on service provided by the government social insurance company engaged in traffic accident insurance services in Surabaya. As an industry that provides service, customer satisfaction is of importance in order to gain trust from the public, reduce negative opinion in public, and support the objective of good governance. This study integrated the SERVQUAL-Kano method to evaluate customer satisfaction concerning 18 service attributes related to service provided by the social insurance company. Further efforts were then made to find solutions for service attributes with low satisfaction scores by using the Quality Function Deployment (QFD) method. Therefore, the results can help to improve the quality of service. The results were in the form of a priority improvement design for strategic decision recommendations that can be implemented by the company to increase customer satisfaction.